(untitled) (Medical Forum Monthly, 2023)
Objective: Bladder tumor’s treatment with bipolar transurethral resection have been considered as better alternative due to lesser complications and better quality of specimen. The present study aimed to assess the safety and efficacy of bipolar energy for transurethral resection of bladder tumor. Study Design: A prospective study Place and Duration of Study: This study was conducted at the department of Urology in Sahiwal Teaching Hospital, Sahiwal during the period from April 2022 to March 2023. Materials and Methods: This study was conducted on 90 patients underwent transureththeral resection of bladder tumor. All the patients underwent surgery under general anesthesia and were categorized into two groups: Group-I (Mono-polar TURBT) and Group-II (Bipolar TURBT). The demographic details, tumor characteristics, and procedure’s complications such as bladder perforation, transurethral resection syndrome, obturator jerk, blood loss, and need for re-surgery were recorded. The specimens of tumor were analyzed for deep muscle invasion, stage, thermal artifact’s quality and quantity, and grade. Results: Each group had 45 patients. The overall mean age of group-I and group-II patients was 56.48 ± 11.84 years and 55.68 ± 16.92 years. There were 74 (82.2%) male and 16 (17.8%) females. The baseline characteristics and tumor features were comparable in both groups. The prevalence of bladder perforation and variation in hemoglobin levels were comparable. The major complication obturator jerk was found in 26.7% patients as compared to 13.3% in mono-polar group. There were no thermal artifacts in 28.8% patients of group-II as compared to 6.7% in group-I. Conclusion: Bipolar TURBT has the same operating risks as mono-polar TURBT, including as bladder perforation, blood loss, and obturator jerk. However, fewer thermal artefacts in tissue samples obtained via bipolar resection may aid pathologists in interpreting histopathological findings.